Akhir Zaman: Representasi Fenomena Alam dan Sosial melalui Komposisi Kacapi - Yulaeliah, Ela (Institut Seni Indonesia Yogyakarta, 2023)
ABSTRACTThe End of Time: Representations of Natural and Social Phenomena through Kacapi Kawih Composition. The objective of this study is to analyze the results of a composition entitled End Times as a representation of natural and social phenomena. The method proposed by Alma W. Hawkins used in the process of creating this work include exploration, improvisation, and formation. The work entitled End Times is inspired by various natural and social phenomena that occur in society, such as volcanic eruption, flood, tsunami, and even covid-19 that boomed recently. Furthermore, the social order of society is increasingly uncertain due to war, assassination, and even oppression by the powerful over the weak. These are signs or characteristics of the end of time related to the involvement of mankind in nature. These various phenomena are the source of creativity and inspire the author to create a fresh work in the composition of the Sundanese kacapi kawih entitled